Aerodynamic drag in cycling pelotons: New insights by CFD simulation and wind tunnel testing - Blocken, B.; van Druenen, T.; Toparlar, Y.; Malizia, F.; Mannion, P.; Andrianne, T.; Marchal, T.; Maas, G.-J.; Diepens, J. (Journal of Wind Engineering and Industrial Aerodynamics, 2018)
A cycling peloton is the main group of cyclists riding closely together to reduce aerodynamic drag and energy expenditure. Previous studies on small groups of in-line drafting cyclists showed reductions down to 70 to 50% the drag of an isolated rider at same speed and these values have also been used for pelotons. However, inside a tightly packed peloton with multiple rows of riders providing shelter, larger drag reductions can be expected. This paper systematically investigates the drag reductions in two pelotons of 121 cyclists. High-resolution CFD simulations are performed with the RANS equations and the Transition SST-k-? model. The cyclist wall-adjacent cell size is 20 µm and the total cell count per peloton is nearly 3 billion. The simulations are validated by four wind-tunnel tests, including one with a peloton of 121 models. The results show that the drag of all cyclists in the peloton decreases compared to that of an isolated rider. In the mid rear of the peloton it reduces down to 5%-10% that of an isolated rider. This corresponds to an "equivalent cycling speed" that is 4.5 to 3.2 times less than the peloton speed. These results can be used to improve cycling strategies.